Emotional Connections Between Brands and Consumers in Digital Age - Musyfiqoh, Aminatul; Roosdhani, Mohamad Rifqy (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
This study explores the relationship between social media marketing activities (SMMA), brand love, and purchase decisions in Indonesia’s transportation sector, focusing on PO Bejeu. Social media acts as an interactive medium fostering emotional bonds between brands and consumers, termed brand love. The research reveals that SMMA significantly enhances brand love, which directly impacts purchase decisions. Additionally, social ties mediate this relationship, as interactions on social media strengthen loyalty and influence purchasing behavior. A survey of 103 Facebook community members who actively discuss Bejeu products was conducted, with data analyzed using the SEM-PLS method, confirming the validity and reliability of all variables. Results indicate full mediation between SMMA and purchase decisions via brand love and partial mediation through social ties. These findings underscore the strategic role of SMMA in cultivating emotional connections to boost loyalty and purchases. The study suggests further research into brand love dynamics across diverse cultural and industrial settings to expand understanding.